Primary pulmonary myxoid sarcoma: A case report and review of the literature - Hollis Hutchings; Erik Schwarze; Beena Ahsan; Jessica Cox; Ikenna Okereke (Global Journal of Perioperative Medicine - Peertechz Publications, 2023)
Background: Primary pulmonary myxoid sarcoma is a very rare tumor, with less than 25 cases being described in the literature. When found in the bronchial tree, an R0 resection with post-operative follow-up is sufficient for curative treatment. We present a case of primary pulmonary myxoid sarcoma in a middle-aged man with an associated review of the literature to highlight this rare tumor. Case presentation: A 62-year-old man with a 40-pack-year smoking history presented to the thoracic surgery clinic for evaluation of a suspicious lung nodule. Pre-operative testing revealed a spiculated mass in the left upper lobe and the biopsy was non-diagnostic. The patient was taken for left upper lobectomy tri-segmentectomy with mediastinal lymph node dissection. Final pathology of the nodule revealed primary pulmonary myxoid sarcoma with an Ewing sarcoma breakpoint region 1 on chromosome 22 with activating transcription factor 1 (EWSR-ATF1) fusion transcript consistent with the diagnosis.  Conclusion: Primary pulmonary myxoid sarcoma is an exceedingly rare sarcoma of the lung with less than 25 reported cases in the literature. This case report highlights our experience treating primary pulmonary myxoid sarcoma in a middle-aged man, and a review of current treatment recommendations in the available published literature.